PENDETEKSI KELAYAKAN KADAR GAS EMISI KENDARAAN - , RIZKY AGUSTIAN PURDIANTORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Strong growth in demand for cars , air pollution will reduce the quality of human health . One of the pollutants generated by motor vehicle emissions are carbon monoxide ( CO ) and nitrogen oxides ( NOx ) .CO gas and NOx gas can cause health problems for humans , even if exposed to the concentration limits specified period of time and can lead to death . Emission test device has been available in many auto repair shops , but by the time the emissions test , just read the source or sources of gas emissions from the exhaust vent . This final project aims to design a carbon monoxide detector and nitrogen oxides detector, that device will indicate the level of carbon monoxide ( CO ) and nitrogen oxides ( NOx ) into 3 categories of air quality , safe , and the danger threshold . the system will automatically warn the driver if the gas exceeds the threshold . microcontroller is used as the central data processing center and the data is ATMega8 microcontroller gas sensor using MQ-7 and MQ-135. The design begins with the schame of hardware and software design using CVAVR and proteus 7 professional.the testing phase is done by using gas by testing tool using a source from exhaust vent. There are three actuators , the LCD will display the levels of CO gas and NOx gas , the Buzzer will give a warning buzzer sounds when gas exceeds the threshold , and the LED will give an indication of certain conditions .